Anaerobic digestion for cattle manure treatment and its kinetic modelling in an oscillatory flow biogas reactor - Muhammad Nasir, Ismail (2016)
Anaerobic digestion of animal manure is gradually becoming essential as a means of protecting the environment and recycling materials efficiently into the farming systems. Over the last few decades, efforts have been made for treating dairy cattle manure according to the growing 'waste to energy' recycle notion in engineered bioreactors, rather than collecting in lagoons or left to decompose in the open which cause a significant environmental hazard. There are quite a number of bioreactors operating at commercial animal manure facilities and allow for the recovery of clean energy 'biogas' from waste without methane emissions into the atmosphere, which cause adverse greenhouse effects. Majority of these projects generate electricity and or capture the waste heat for different in-house requirements. Various reactor design configurations for the anaerobic treatment of cattle manure at the laboratory scale and full-scale have been applied and their performance evaluated. Recent developments in mixing technology has developed a new way of mixing substrates by introducing an oscillatory motion to replace the conventional mechanical agitation or an air bubble displacement. This mixing is referred to as oscillatory flow mixing (OFM), which relatively provides good mixing and a range of specific process enhancements, such as improved mass transfer, heat transfer, and narrow residence time distribution. The main aim of this research was to evaluate the potential biogas and methane production in the anaerobic digestion of cattle manure using a novel reactor design. A novel oscillatory flow biogas reactor (OFBR) was used to assess the impact of various organic loading rate variation, as well as different HRT, on the OFBR operation. Experiments were conducted in both batch and semi-continuous mode using a 6 L bioreactor, under thermophilic condition (55°C). The process performance was assessed using various parameters such as: volatile solids (VS) and chemical oxygen demand (COD) removal, biogas and methane production and yields. Whereas, the digestate quality was monitored with the following parameters: VS, pH, volatile fatty acids (VFA), and ammonia nitrogen (NH3-N) concentration. Initially, batch experiments were conducted in order to assess the first start-up of the cattle manure digestion. Moreover, they provided digestate for the succeeding semicontinuous studies, in addition to providing vital information regarding ultimate process efficiency in terms of biogas and methane yield and solids removal. Furthermore, rapid start-up batch experiments were used to determine the required HRT for semi-continuous studies. Optimum organic loading rate (OLR) was determined with the use of the OFBR semi-continuous process. The optimum OLR was found to be 2.4 g VS/L/day based on the operational conditions set for this study, at which maximum volumetric biogas production of 5.2 L per L reactor per day and methane production of 3.13 L per L reactor per day were achieved during the phase one of the semi-continuous study. According to the results obtained in the phase two of the semi-continuous study, the process performance observed at HRT of 12 days were similar to the first organic loading (1.3 g VS/L/day) in the phase one study at HRT of 18 days. This showed that the operational conditions in the phase two experiment might be more desirable economically than in the phase one in relation to reducing operational cost and bioreactor volume. Finally, a steady-state mathematical model was developed; based on the Contois bacterial growth kinetics, describing the methane production rate of the semicontinuous operation of the OFBR utilising data produced and a novel kinetic approach. The best fit values for the maximum specific growth rate (μm) and dimensionless kinetic parameter (K) were found as 0.2 day–1 and 0.8, for phase one, and 0.22 day–1 and 0.84, for phase two, respectively. In addition, under the studied experimental conditions, the sum of the residual error of the predictions of Chen and Hashimoto’s model (R2 =0.84) using their recommended kinetic parameters (μm = 0.326; K = 0.81) had a good correlation with the experimental results in phase 2 (R2 =0.85). Therefore, the findings from this study recommend that each anaerobic digester for manure treatment should be evaluated and designed individually to effectively serve its purpose, rather than random application of the manure digestion models and their proposed kinetic parameters which may lead to significant error in the prediction of methane production rate. The overall performance of the OFBR proved that the design is suitable for the anaerobic digestion of the cattle manure by providing successful manure treatment, based on VFA, VS and COD removal, for all operational modes examined in this study.